Intervensi Edukasi Stunting di Desa Sidera, Kabupaten Sigi, Sulawesi Tengah - Kamaludin, Tutang Muhtar; Adrianton, Adrianton; Pardosi, Restu; Labombang, Mastura; Fadjar, Adnan; F, Fahirah; Susilawati, Susi (JATIMAS : Jurnal Pertanian dan Pengabdian Masyarakat, 2024)
Stunting in children is still a major challenge in Indonesia, including in rural areas such as Sidera Village, Sigi Regency, Central Sulawesi. The Thematic Community Service Program (KKN) on Stunting aims to assist the government's efforts to accelerate the reduction in stunting rates by providing the community with education related to stunting prevention. Through this KKN, Tadulako University students are involved in activities integrating the Tri Dharma of Higher Education, especially in community service and student competency development. The methods included field observation, direct education, and collaboration with local health counsellors. Observations are carried out to identify factors that cause stunting, such as environmental conditions and nutritional parenting patterns in children. Counselling provides education on the importance of nutritional intake, environmental cleanliness, and healthy eating patterns as preventive measures. The results of the activities show an increase in community knowledge about the causes of stunting and intervention steps that can be taken to reduce the risk of stunting. In conclusion, this program has succeeded in increasing awareness in the Sidera Village community about the importance of stunting prevention. It is expected to be an effective education model for other areas. Stunting pada anak masih menjadi tantangan besar di Indonesia, termasuk di wilayah pedesaan seperti Desa Sidera, Kabupaten Sigi, Sulawesi Tengah. Program Kuliah Kerja Nyata (KKN) Tematik Stunting bertujuan membantu upaya pemerintah dalam percepatan penurunan angka stunting dengan memberikan edukasi terkait pencegahan stunting kepada masyarakat. Melalui KKN ini, mahasiswa Universitas Tadulako terlibat dalam serangkaian kegiatan yang mengintegrasikan Tri Dharma Perguruan Tinggi, khususnya dalam bidang pengabdian masyarakat dan pengembangan kompetensi mahasiswa. Metode yang digunakan mencakup observasi lapangan, edukasi langsung, serta kolaborasi dengan penyuluh kesehatan setempat. Observasi dilakukan untuk mengidentifikasi faktor penyebab stunting, seperti kondisi lingkungan dan pola asuh gizi pada anak. Edukasi diberikan dalam bentuk penyuluhan tentang pentingnya asupan gizi, kebersihan lingkungan, dan pola makan sehat sebagai langkah preventif. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan masyarakat mengenai penyebab stunting serta langkah- langkah intervensi yang dapat dilakukan untuk menurunkan risiko stunting. Kesimpulannya, program ini berhasil meningkatkan kesadaran masyarakat Desa Sidera tentang pentingnya pencegahan stunting dan diharapkan dapat menjadi model edukasi yang efektif bagi wilayah lainnya.